Влияние исследования и эксплуатации космических природных ресурсов на Индонезию с точки зрения аспектов национального права (The Legal Implications of Exploration and Exploitation of Space Natural Resources for Indonesia) - Laurentius Raymond Junior; Athari Farhani (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The commercialization of space in this century has become a new phenomenon that includes all kinds of activities that lead to exploration and even exploitation in space. These activities are carried out by the private sector or certain countries that have advanced technology capabilities in conducting exploration in space. Exploration activities in space are not only limited to the placement of remote sensing satellites, astronomical observations, power plants, or communication facilities but also led to the exploitation of natural resources in space. This certainly has an impact on Indonesia considering that national legal guarantees are not yet comprehensive in regulating space. Therefore this research was conducted to analyze how national laws regulate aspects of space and how the impact of exploration and exploitation of natural space resources for Indonesia. The results of this study illustrate that the existence of space has an important role for every country, especially Indonesia. Considering the existence and rapid development of space, Indonesia needs to provide a more comprehensive legal guarantee in regulating space, especially in the use of natural space resources.Keywords: Space; Exploration and Exploitation; Natural Resources Dampak Eksplorasi dan Eksploitasi Sumber Daya Alam Ruang Angkasa Bagi Indonesia Ditinjau Dari Aspek Hukum Nasional AbstrakKomersialisasi ruang angkasa di abad ini menjadi fenomena baru yang meliputi segala macam aktivitas yang mengarah pada eksplorasi bahkan eksploitasi di ruang angkasa. Aktivitas tersebut dilakukan oleh swasta maupun negara tertentu yang memiliki kemampuan teknologi canggih dalam melakukan penjelajahan di ruang angkasa. Kegiatan eksplorasi di ruang angkasa tidak hanya sebatas pada penempatan satelit penginderaan jarak jauh, observasi astronomi, pembangkit tenaga, atau sarana komunikasi namun juga sudah mengarah pada eksploitasi sumber daya alam di ruang angkasa. Hal tersebut tentu memberikan dampak bagi Indonesia mengingat jaminan hukum nasional belum begitu komprehensif mengatur berkenaan dengan ruang angkasa. Maka dari itu penelitian ini dilakukan untuk menganalisis bagaimana hukum nasional mengatur aspek ruang angkasa serta bagaimana dampak eksplorasi dan eksploitasi sumber daya alam ruang angkasa bagi Indonesia. Adapun hasil dari penelitian ini memberikan gambaran bahwa keberadaan ruang angkasa memiliki peranan penting bagi setiap negara, khususnya Indonesia. Mengingat keberadaan serta perkembangan ruang angkasa begitu pesat, sehingga Indonesia perlu memberikan jaminan hukum yang lebih komprehensif dalam pengaturan ruang angkasa khususnya dalam pemanfaatan sumber daya alam ruang angkasa.Kata Kunci : Ruang Angkasa; Eksplorasi dan Eksploitasi; Sumber Daya Alam. Влияние исследования и эксплуатации космических природных ресурсов на Индонезию с точки зрения аспектов национального права АннотацияКоммерциализация космоса в этом столетии стала новым явлением, которое включает в себя все виды деятельности, ведущие к исследованию и даже эксплуатации космоса. Подобные действия осуществляются частным сектором или некоторыми странами, которые обладают передовыми технологическими возможностями для проведения исследований в космосе. Исследовательская деятельность в космосе не только ограничивается размещением спутников дистанционного зондирования, астрономическими наблюдениями, электростанциями или средствами коммуникации, но также ведет к эксплуатации природных ресурсов в космосе. Это, безусловно, влияет на Индонезию, учитывая, что национальные правовые гарантии еще не являются исчерпывающими в регулировании космоса. Таким образом, это исследование было проведено для анализа того, как национальное законодательство регулирует аспекты космоса и как влияют исследование и эксплуатация природных космических ресурсов на Индонезию. Результаты этого исследования показывают, что существование космоса играет важную роль для каждой страны, особенно для Индонезии. Учитывая существование и быстрое развитие космоса, Индонезии необходимо предоставить более всеобъемлющие правовые гарантии в регулировании космоса, особенно в использовании природных космических ресурсов.Ключевые слова: Космос, исследование и эксплуатация, природные ресурсы